COVID-19 in Children: Respiratory Involvement and Some Differences With the Adults - Jenny Libeth Jurado Hernández; Iván Francisco Álvarez Orozco (Frontiers Media S.A., 2021)
The coronavirus disease 2019 (COVID-19) represents a health problem with multidimensional impacts and heterogeneous respiratory involvement in children, probably due to the interaction between different and complex mechanisms that could explain its variable degrees of severity. Although the majority of reports reveal that children develop less severe cases, the number of patients is increasing with more morbidity. Most serious respiratory manifestations are acute respiratory distress syndrome (ARDS) and pneumonia. By understanding the key aspects that can be used to differentiate between pediatric and adult respiratory compromise by COVID-19, we can improve our knowledge, and thus decrease the negative impact of the disease in the pediatric population. In this mini review, we summarize some of the mechanisms and findings that distinguish between adult and pediatric COVID-19 and respiratory involvement, taking into account some issues related to the physiopathology, diagnosis, clinical and paraclinical presentation, severity, treatment, and control of the disease.